2015
DOI: 10.1161/strokeaha.115.010537
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Induced Hypertension on Cerebral Perfusion in Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-The presumed effectiveness of induced hypertension for treating delayed cerebral ischemia after aneurysmal subarachnoid hemorrhage is based on uncontrolled case-series only. We assessed the effect of induced hypertension on cerebral blood flow (CBF) in aneurysmal subarachnoid hemorrhage patients with delayed cerebral ischemia in a randomized clinical trial. Methods-Aneurysmal subarachnoid hemorrhage patients were randomized to induced or no induced hypertension (control group) at delayed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
3
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 5 publications
2
53
3
2
Order By: Relevance
“…They found that raising BP an average of 12 mm Hg did not change global or CBF or CBF asymmetry in the region with the lowest baseline flow. [42]…”
Section: Discussionmentioning
confidence: 99%
“…They found that raising BP an average of 12 mm Hg did not change global or CBF or CBF asymmetry in the region with the lowest baseline flow. [42]…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic interventions are routinely employed for this purpose, including volume expansion, induced hypertension, and augmentation of cardiac output [24]. Still, optimal management of DCI remains largely empiric, with no therapeutic strategies being supported by clinical or even convincing physiologic proof-of-efficacy [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…It appears that MTT, not CBF, is the key component both to identify those more likely to develop DCI, but also for monitoring the effect of treatment. The authors were able to show a significant change with MTT with one-tenth the patients that have been thought to be needed for a trial of IH if one is looking for changes in CBF [7]. This paper, like others, did not find clinical differences in the DCI versus the non-DCI cohorts.…”
mentioning
confidence: 61%